2014
DOI: 10.1080/10407782.2013.846607
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Unsteady Natural Convection from Heated Horizontal Circular Cylinders in a Square Enclosure

Abstract: In this article, a 2-D numerical study is carried out to investigate the effect of this interaction on natural convection from two heated horizontal cylinders confined in a square enclosure with isothermal walls at the heat sink temperature. The simulations are carried out for Rayleigh numbers between 10 3 and 10 7 , and dimensionless horizontal distances of cylinders between 0.1 and 0.4. The results show that the variation of the area-averaged Nusselt number strongly depends on the distance between the two cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Karimi et al [13] carried out numerical research similar to that of Lacroix [12]. They carried out numerical simulation of natural convection from two heated horizontal cylinders in a cold square enclosure.…”
Section: Introductionmentioning
confidence: 97%
“…Karimi et al [13] carried out numerical research similar to that of Lacroix [12]. They carried out numerical simulation of natural convection from two heated horizontal cylinders in a cold square enclosure.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, rooted from the gas kinetics, LBM is considered as a persuasive numerical technique tool in casting hydrodynamics in fluid flows in various engineering fields . Recently, it has been extended to simulate free convection in a considerable variety of complex dynamic and thermal behaviors, relayed on the temperature difference between the inner and outer bodies, the sizes and shapes of the inner bodies, their arrangement and their position . The most prominent model, lattice Bhatnagar‐Gross‐Krook (BGK) is used in this paper, which approximates the collision operator normalΩα=ω[fα(r,t)fαeq(r,t)] as a relaxation of the distribution function fαfalse(truer,tfalse) towards a local equilibrium distribution fαeq(r,t).…”
Section: Simulation Method: Lbmmentioning
confidence: 99%
“…These studies were motivated by the desire to understand the fundamental physics and free convection characterization inside the cavity that can be influenced and affected by the sizes and shapes of the interior bodies, their number, position, arrangement, and also the configuration of the cavity . So, due to its substantial significance, heat transfer with free convection in presence of heating cylinders is investigated by many researchers .…”
Section: Introductionmentioning
confidence: 99%
“…Together with the experimental studies reported recently [14][15][16][17][18], there are also numerical simulations [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], some based on the k-ε turbulence model [19][20][21] or direct numerical simulation (DNS) [22][23][24][25][26][27][28][29][30][31][32], with others by means of large eddy simulation (LES) [33,34]. For turbulent flow simulations, three strategies, phenomenological modeling [35,36], DNS [37], and LES [38], are usually employed.…”
Section: Introductionmentioning
confidence: 99%